Direct Comparison of C-H Bond Amination Efficacy through Manipulation of Nitrogen-Valence Centered Redox: Imido versus Iminyl - Wilding, Matthew J. T.; Iovan, Diana A.; Wrobel, Alexandra T.; Lukens, James T.; MacMillan, Samantha N.; Lancaster, Kyle M.; Betley, Theodore A. (Journal of the American Chemical Society, 2017)
Reduction of previously reported iminyl radical (L-Ar)FeC1(center dot N(C6H4-p-Bu-t)) (2) with potassium graphite furnished the corresponding high-spin (S = 5/2) imido (L-Ar) F e (N(C6H4-p-Bu-t)) (3) (L-Ar = 5-m esityl-1,9-(2,4,6-Ph3C6H2)dipyrrin). Oxidation of the three-coordinate imido (L-Ar)Fe(NAd) (5) with chlorotriphenylmethane afforded (L-Ar)FeCl(center dot NAd) (6) with concomitant expulsion of Ph3C-(C6H5)CPh2. The respective aryl/alkyl imido/iminyl pairs (3, 2; 5, 6) have been characterized by EPR, zero-field Fe-57 Mossbauer, magnetometry, single crystal X-ray diffraction, XAS, and EXAFS for 6. The high-spin (S = 5/2) imidos exhibit characteristically short Fe N bonds (3: 1.708(4) angstrom; 5: 1.674(11) angstrom), whereas the corresponding iminyls exhibit elongated Fe N bonds (2: 1.768(2) angstrom; 6: 1.761(6) angstrom). Comparison of the pre-edge absorption feature (ls -> 3d) in the X-ray absorption spectra reveals that the four imido/iminyl complexes share a common iron oxidation level consistent with a ferric formulation (3: 7111.5 eV, 2: 7111.5 eV; 5: 7112.2 eV, 6: 7112.4 eV) as compared with a ferrous amine adduct (L-Ar)FeCl(NH(2)Ad) (7: 7110.3 eV). N K-edge X-ray absorption spectra reveal a common low-energy absorption present only for the iminyl species 2 (394.5 eV) and 6 (394.8 eV) that was assigned as a N is promotion into a N-localized, singly occupied iminyl orbital. Kinetic analysis of the reaction between the respective iron imido and iminyl complexes with toluene yielded the following activation parameters: Ea (kcal/mol) 3: 12.1, 2: 9.2; 5: 11.S, 6: 7.1. The attenuation of the Fe N bond interaction on oxidation from an imido to an iminyl complex leads to a reduced enthalpic barrier [Delta(Delta H-double dagger) approximate to 5 kcal/mol]; the alkyl iminyl 6 has a reduced enthalpic barrier (1.84 kcal/mol) as compared with the aryl iminyl 2 (3.84 kcal/mol), consistent with iminyl radical delocalization into the aryl substituent in 2 as compared with 6.